2021
DOI: 10.12998/wjcc.v9.i32.9741
|View full text |Cite
|
Sign up to set email alerts
|

Effects of early rehabilitation in improvement of paediatric burnt hands function

Abstract: BACKGROUND Hands are one of the most common burn sites in children. Hypertrophic scar contractures in hands after wound healing result in further reductions in their range of motion (ROM), motility, and fine motor activities. Rehabilitation can improve the function of hands. But the optimal time of rehabilitation intervention is still unclear. Therefore, this study was designed to investigate the effects of early rehabilitation management of paediatric burnt hands and to compare the efficacy betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
1
0
1
Order By: Relevance
“…Clinical practice has shown that early application of braces to maintain body position and prevent scar contraction can reduce obvious joint deformities, and the recovery of joint function is obviously better than that of patients who started treatment late, only after joint contraction appeared (30)(31)(32). We attempted to assist hand positioning with braces during the NPWT process, even using a thin and low-temperature thermoplastic material (which can be appropriately placed in shape under negative pressure) to maintain thumb abduction and a functional hand position.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical practice has shown that early application of braces to maintain body position and prevent scar contraction can reduce obvious joint deformities, and the recovery of joint function is obviously better than that of patients who started treatment late, only after joint contraction appeared (30)(31)(32). We attempted to assist hand positioning with braces during the NPWT process, even using a thin and low-temperature thermoplastic material (which can be appropriately placed in shape under negative pressure) to maintain thumb abduction and a functional hand position.…”
Section: Discussionmentioning
confidence: 99%
“…La rehabilitación de las quemaduras durante la etapa aguda debe centrarse en la reducción del edema de la herida, el mantenimiento de la posición anti-contractura y los ejercicios en rango de movimiento pasivo asistido por el fisioterapeuta y rango de movimiento activo ejecutados únicamente por el paciente, pero bajo la supervisión del fisioterapeuta (23).…”
Section: Ejerciciounclassified